(untitled) (Alternautas, 2022)
Hurricanes are the hazard most synonymous with the Caribbean and have, consequently, received the most attention from historians. Yet, they have tended to be considered exogenous phenomena. There has been little attention paid to the role endogenous factors have played in exacerbating the potential for loss from hurricane impacts. Through a comparison of the impacts of the Barbadian hurricane of 1831 and the Dominican hurricane of 1834 this article seeks to advance the existing literature by examining the role the plantation played in exacerbating hurricane vulnerability. In revealing the significantly contrasting amount of damage these islands sustained, this article shows that, at least in this case, the more expansive plantation agriculture of Barbados exposed its habitants to far greater human, economic and environmental losses.